The Dynamics of Service Delivery and Agricultural Development in India - A District-Level Analysis - - Katharina Raabe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper uses district-level data from India for the Census period 1991-2001 to investigate the nexus between agricultural sector development and service delivery in education, health, transportation, and communication. It asks whether local differences in public service provision cause some districts to fare better in terms of agricultural and ultimately rural development than others. In order to control for regional heterogeneities in agro-ecological conditions and consequent heterogeneities in agricultural potential and development, district agricultural sector performance is approximated with the yield level of district-specific commercial and field crops. The evidence from visualization and standard regression techniques shows that district dissimilarities in crop yield and ultimately agricultural development are not attributable to district differences in the endowment with infrastructure facilities. That is, the number of infrastructure facilities does not explain agricultural development. What seems to be more important instead is the quality of rural services. This paper concludes that progress in agricultural and ultimately rural sector performance does not require more infrastructure facilities, but the effective utilization of existing ones. To this end, the supply side of service delivery needs to be investigated in greater detail, especially with respect to the governance challenges of public service provision and the difficulties arising from, for instance, complex administrative structures or manpower, financial, political, and capacity constraints.
Keywords: H7; O1; O16; P2; R1; 330; Agricultural development; rural service delivery; India